(MIS)READING THE GNAT: TRUTH AND DECEPTION IN THE PSEUDO-VIRGILIAN CVLEX. (December 2018) - Kearey, Talitha
Abstract : The Culex —the earliest and best attested of the purported minor works of Virgil, and the most outright in gesturing towards Virgilian authorship—poses a problem for modern classical scholarship. Since at least the seventeenth century scholars have been preoccupied with the poem's authenticity. Is it a piece of early Virgilian iuuenilia, as the ancient testimonies and mediaeval transmission of the text seem to assert, or a later production? If a later production, should we see it as a deliberate forgery, or as a poem severed in the course of transmission from its original author and helplessly swept up in Virgil's train? The authenticity problem has proven persistent: as recently as the 1970s, scholars tried to claim the Culex for Virgil. Even among those who think it non-Virgilian, the apparent consensus of anonymous late-Tiberian authorship has been contested by Otto Zwierlein's suggestion of M. Julius Montanus and Jean-Yves Maleuvre's, even more unlikely, of Augustus.